2006
DOI: 10.3200/bmed.32.2.36-46
|View full text |Cite
|
Sign up to set email alerts
|

Age Group and Health Status Effects on Health Behavior Change

Abstract: The authors explored health behavior change during 5 years, considering age/cohort, health status, and gender effects. The authors divided the sample (n = 1,064) into 4 age/cohort groups: young adults (n = 139; 19-42 years), middle-aged adults (n = 386; 43-62 years), young-old adults (n = 296; 63-72 years), and old-old adults (n = 243; 73+ years) and health status: cardiovascular disease and physical disability. Smoking and seat belt behaviors remained stable, whereas alcohol, food consumption, food preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 6 publications
1
38
1
Order By: Relevance
“…Other studies have reported temporary reductions in smoking, drinking and body weight [9, 11, 36], paired with rising leisure physical activity during economic contractions. Given that the age around the transition from school to work is a critical period for initiation or cessation of behaviors such as smoking [37-39], recessions around this period may not only have temporary effects, but also delay or prevent initiation of these behaviors altogether [5]. In addition, leaving school during a period of high unemployment may also delay entrance into the labor market [36], reducing the likelihood of entering jobs with hazardous working conditions at young age, particularly for lower-educated men.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported temporary reductions in smoking, drinking and body weight [9, 11, 36], paired with rising leisure physical activity during economic contractions. Given that the age around the transition from school to work is a critical period for initiation or cessation of behaviors such as smoking [37-39], recessions around this period may not only have temporary effects, but also delay or prevent initiation of these behaviors altogether [5]. In addition, leaving school during a period of high unemployment may also delay entrance into the labor market [36], reducing the likelihood of entering jobs with hazardous working conditions at young age, particularly for lower-educated men.…”
Section: Discussionmentioning
confidence: 99%
“…Participants defi ned as "consistently healthy" were those who reported no health care professional diagnoses of heart disease, cancer, stroke, or diabetes for the fi rst two cycles (Figure 1). These conditions were chosen because they may lead to changes in health behavior, such as reduced alcohol use (Chiuve et al, 2006;Khaw et al, 2008;Morley and Flaherty, 2002;Zanjani et al, 2006). In addition, consistently healthy participants had to report being in good to excellent health in the fi rst two cycles (response options for self-rated health were excellent, very good, good, fair, or poor).…”
Section: Methodsmentioning
confidence: 99%
“…These studies, however, were limited in that they failed to address how changes in lifestyle-related factors are associated with the incidence of proteinuria. Lifestyles change throughout life, even in the elderly stages (12). …”
Section: Introductionmentioning
confidence: 99%